Emotional transformation through the effects of somatic therapy techniques in reducing depression among students of skill training institutions - Norizan, Yusof (Universiti Malaysia Pahang, 2025)
Depression among students of higher education institutions is an increasingly worrying issue, with negative effects on mental well-being and academic performance. This study aims to evaluate the effectiveness of somatic therapy techniques in reducing depression levels and improving students' emotional well-being. Somatic therapy focuses on the relationship between the body and emotions through movement, breathing, and body awareness techniques to reduce psychological stress. This study uses quantitative and qualitative approaches, involving a sample of students with mild to moderate depressive symptoms. Data were collected through questionnaires, semi-structured interviews, and behavioral observations before and after an eight-week somatic therapy intervention. The results of the study showed a significant decrease in participants' depression levels, increased emotional awareness, and increased ability to control stress. Somatic therapy was found to be an easy-to-practice and effective method in reducing depression. This study suggests that somatic therapy should be made part of mental health intervention strategies in higher technical education institutions.